Detection of structural breaks in linear dynamic panel data models - Stefan de Wachter; Elias Tzavalis (Queen Mary University of London, Department of Economics, 2004)
This paper develops a break detection procedure for the well-known AR(p) linear panel data model with exogenous or pre-determined regressors. The test allows for a structural break in the slope parameters as well as in the fixed effects. Breaks in the latter are not constrained by any type of cross-sectional homogeneity and are allowed to be correlated with all past information.
Keywords: C23; 330; Panel data; Structural break; Break detection; Panel; Strukturbruch; Mathematische Optimierung